Optimasi Budidaya Bawang Merah Secara Organik dengan Formulasi Kompos Gulma Siam Berbasis Agens Hayati - Bambang Nugroho; Warmanti Mildaryani; Dian Astriani (Politeknik Negeri Lampung., 2024)
Conventional shallot cultivation has brought negative effects such as chemical pollution, decrease in biodiversity, and fungal pathogen resistance. The use of organic fertilizer and biopesticides is a good solution to overcome the problems. This research was done to find optimum dose of siam weed compost combined with biocontrol of avirulent Fusarium oxysporum f. sp. cepae on shallot production. A single factor arranged in Randomized Complete Design with 3 replications was used. The treatment was the dose of siam weed compost i.e. A = control, B = 5 tons/ha, C = 10 tons/ha, D = 15 tons/ha, and E = 20 tons/ha. Siam weed compost was enriched with the biocontrol before used. The results showed that up to 20 tons/ha, siam weed compost increased only shallot growth of fresh and dry weight of plant. There was no significant effect to shallot yield. Incidence of moler disease was very low during the research.